INTENSITAS SERANGAN HAMA PENGGEREK BUAH KOPI (Hypothenemus hampei Ferr ) DAN UPAYA PENGENDALIANNYA - Sasmita Sari (Program Studi Agribisnis Fakultas Pertanian, 2023)
Arabica coffee (Coffea arabica L.) is a type of coffee that has been widely developed in Indonesia because of its relatively better quality and price compared to other types of coffee. Currently, the increase in coffee production in Indonesia is hampered by the low productivity and quality of coffee produced. One of the reasons for the low productivity and quality of coffee in Indonesia is the disturbance of various pest attacks by Hypothenemus hampei Ferr. PBKo pest control is quite difficult because the insects are found in the coffee cherries. The H. hampei insect is known to only attack and reproduce on coffee cherries. Therefore, observations of PBKo pests must be carried out to determine populations, attack levels and control efforts, namely using antractant compounds. The method used is direct observation method. The study used a factor randomized block design. Based on the results of the discussion it is known that the number of pests trapped in traps containing antractant compounds fluctuates or decreases. So when the test was carried out using the BNT level of 5% it was not significantly different. The use of attractant as a pest trap on coffee plantations aged 9 years was able to reduce the intensity of attack by the pest Hypothenemus hampei Ferr from the heavy attack intensity category to the light attack intensity category. Keywords : Arabica Coffee, Hypothenemus hampei Ferr. and antractan